The Influence of the Implementation of the Policy on the Implementation of Regional Government Affairs on the Regional Government Administration Report - Setiadi, Ade; Muhafidin, Didin; Rohadin; Melliyanawati, Dwi (International Journal of Science and Society, 2025)
Implementing policies related to regional government affairs significantly impacts the administration and reporting processes within local governance structures. This study investigates the influence of such policies on the Regional Government Administration Report (LPPD) at the Governance Section of the Regional Secretariat of Indramayu District. By employing a mixed-methods approach, combining both quantitative and qualitative data collection techniques, the research aims to understand how policy implementation affects the effectiveness and accuracy of the LPPD. A comprehensive literature review was conducted to establish a theoretical framework, drawing on critical concepts in policy implementation and regional governance. The study's population includes officials and administrators within the Governance Section, with data collected through surveys and interviews. The findings reveal that effective policy implementation positively correlates with the quality of the LPPD, highlighting key factors such as resource allocation, training, and stakeholder engagement. However, challenges such as bureaucratic inertia and limited technical capacity were also identified as barriers to optimal implementation. The study concludes by providing practical recommendations for enhancing policy implementation processes and improving the LAPD's role in regional governance. Future research directions are suggested to explore further the dynamics between policy implementation and administrative reporting in other regional contexts.